Immediacy and Feedback in Instructional Communication in Shaping Translation Anxiety and Cognitive Engagement Among EFL Learners - Sujarwo, Sujarwo; Abdul, Nurdevi Bte; Asdar, Asdar; Asia M, Asia M; Zakaria, Fadilah Binti (JOLLT Journal of Languages and Language Teaching, 2026)
This study aims to investigate the complex interplay between instructional communication, translation anxiety, and cognitive engagement among EFL university students participating in a translation course. The study employed an interpretive phenomenological analysis (IPA) design, involving 11 participants who contributed data via semi-structured interviews, classroom observations, and reflective journals. The findings demonstrate that communicative immediacy fosters emotional safety, thereby alleviating learners’ translation anxiety and augmenting their cognitive engagement. When communication is dialogic and helpful, students feel empowered to articulate interpretations, justify linguistic choices, and engage in critical reflection on meaning production. On the other hand, limited or evaluative communication tends to make anxiety worse and make it harder for people to think about things. These results underscore the need to incorporate communication training into translator education to develop emotionally responsive and cognitively engaged learners. Overall, the results show that communication is an important part of translation pedagogy because it turns worry into contemplation and involvement into comprehension. This study concludes that effective instructional communication prioritizes immediacy, empathy, and dialogic interaction and is essential for alleviating translation anxiety and fostering cognitive engagement among EFL learners. The implications currently impact translator education by emphasizing the necessity for communication-focused training to assist teachers in developing more adaptive, reflective, and intellectually engaging translation sessions.